2010
DOI: 10.1016/j.jmps.2010.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of grain size effects on transformation-induced plasticity based on a discrete dislocation–transformation model

Abstract: a b s t r a c tThere is much interest recently in the possibility of combining two strengthening effects, namely the reduction of grain size (Hall-Petch effect) and the transformationinduced plasticity effect (strengthening due to a martensitic transformation). The present work is concerned with the analysis of the combination of these two effects using a discrete dislocation-transformation model. The transformation-induced plasticity mechanism is studied for aggregates of grains of ferrite and austenite of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The grain size was found to have a strong effect on the transformation behavior of austenitic grains, and two contradictory conclusions could be found on this grain size effect in the previous research (Somani et al, 2009;Huang et al, 2011;Iwamoto and Tsuta, 2000;Shi et al, 2010b). Somani et al (2009) and Huang et al (2011) reported that martensite transformation could be enhanced significantly by ultra-fined austenite grains in 301LN stainless steel, which was contrary to the common observations that smaller austenite grains are more stable against transformation (Iwamoto and Tsuta, 2000;Shi et al, 2010b).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The grain size was found to have a strong effect on the transformation behavior of austenitic grains, and two contradictory conclusions could be found on this grain size effect in the previous research (Somani et al, 2009;Huang et al, 2011;Iwamoto and Tsuta, 2000;Shi et al, 2010b). Somani et al (2009) and Huang et al (2011) reported that martensite transformation could be enhanced significantly by ultra-fined austenite grains in 301LN stainless steel, which was contrary to the common observations that smaller austenite grains are more stable against transformation (Iwamoto and Tsuta, 2000;Shi et al, 2010b).…”
Section: Introductionmentioning
confidence: 71%
“…The grain size was found to have a strong effect on the transformation behavior of austenitic grains, and two contradictory conclusions could be found on this grain size effect in the previous research (Somani et al, 2009;Huang et al, 2011;Iwamoto and Tsuta, 2000;Shi et al, 2010b). Somani et al (2009) and Huang et al (2011) reported that martensite transformation could be enhanced significantly by ultra-fined austenite grains in 301LN stainless steel, which was contrary to the common observations that smaller austenite grains are more stable against transformation (Iwamoto and Tsuta, 2000;Shi et al, 2010b). Other factors, such as strain rate, temperature and stress triaxiality, were also found to have strong influences on TRIP effect: (i) at the low strain rate range (<1/s), TRIP effect happens at earlier strain for higher strain rate, while the maximum volume fraction of martensite decreases with increasing strain rate (Das and Tarafder, 2009;Lee et al, 2014;Prüger et al, 2014;Zaera et al, 2014); (ii) TRIP effect is suppressed with increasing temperature at the low temperature range (77-332 K) (Prüger et al, 2014;Zaera et al, 2014;Lebedev and Kosarchuk, 2000); (iii) increasing stress triaxiality intensifies TRIP effect (Lebedev and Kosarchuk, 2000;Jacques et al, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…While there are some publications (e.g., [31]), which study interaction between sharp interfaces and dislocations, most of the efforts are within PFA.…”
Section: Introductionmentioning
confidence: 99%
“…So this additional strain increment originating from phase transformation is accounted in the development of constitutive behavior of a multiphasic material in order to perfectly simulate the material response in continuum mechanical computation. The approaches describing the evolution of the TRIP during phase transformations can be classified into phenomenological models (Mohr and Jacquemin, 2008), micromechanics-based models (Leblond et al, 1989;Taleb and Sidoroff, 2003;Sun et al, 2009) and discrete dislocation-transformation model (Shi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%